A Study to Check the Readiness of Final-Year Dental Students Vis-à-Vis to a Safe and an Independent Practitioner in Sultanate of Oman Amidst the Recent Pandemic - Triveni Nalawade; Sanjay Saraf; Rachappa Mallikarjuna; Belal Haj-Hamed; Siva Kumar; Nutayla Al Harthy; Mohamed Al Ismaily (Hindawi Limited, 2024)
It is essential for a dental student about to graduate to possess robust fundamentals in both basic and clinical dental science. There should be a perfect harmony and blend of basic and clinical science integration and application among final year graduating students. They should also demonstrate readiness and competence in performing various clinical skills independently, after correctly interpreting and diagnosing a dental disorder. Besides the clinical aspects of dentistry, the newly graduating dental student should understand the principles of professionalism and ethos. The main aim and objective were to conduct a study to assess the impact of COVID-19 on practice readiness among the fifth-year dental students at Oman Dental College (ODC). A study was conducted to measure self-preparedness among graduating students, especially during the challenging times of the COVID-19 pandemic when education was significantly impacted. This study used a validated Dental Undergraduates Preparedness Assessment Scale (DU-PAS). The DU-PAS consists of 50 items, including 24 items related to clinical skills (part A) and 26 items related to scientific knowledge and affective skills (part B). Each item in part A was scored on a three-point scale ranging from no experience (0), with verbal and/or practical input from a colleague (1), to independently (2). Items in part B of the DU-PAS are scored on a three-point scale: no experience (0), mostly (1), and always (2). The maximum score for the 50 items on the DU-PAS is 100. Interestingly, the current study showed that the ODC final-year students were confident in performing several clinical procedures and had a good understanding of various professional aspects of clinical dentistry. The didactic online classes and preclinical sessions conducted while adhering to social distancing and other safety norms during the COVID-19 pandemic, were positively received by the students.